'Let What Happens Happen': The Whitelaw Archive. Issue 2 (September 2016) - Pattie, David
Abstract : This article examines the archival material donated by the estate of Billie Whitelaw to the University of Reading, after the actor's death. The material sheds light on the actress' approach to Beckett's plays, and illuminates the nature of the working relationship between Whitelaw and Beckett. However, the material is also of interest because it sheds light on a series of questions raised by Jonathan Heron and Nicholas Johnson in the recent performance edition of Journal of Beckett Studies ( JOBS 23.1). These questions concern the nature of genetic labour in the archive, as related to performance. In other parts of the archive, genetic labour aims to uncover the stages through which a piece of writing attained its published (or abandoned) form. In the theatre, the process of rehearsal is itself a process of genetic labour, which aims to interrogate, not the author's preferred version of the text, but the version agreed by a number of artists working in collaboration. In the theatre, the question of the actor's performative intention, and the labour through which that intention is realised, is an important part of any archival exploration. The Whitelaw archive is valuable, this article argues, because it enables us to trace the formation of a particular approach to Beckett's texts, undertaken through a process of genetic labour on the texts themselves, rather than on the character or situation that the texts suggest.